Transformasi Kebijakan dan Program Inovatif bagi Peningkatan Mutu Pendidikan Islam - Zaenudin Efendi; Mistam Mistam; Syaharuddin Syaharuddin; Ahmad Sulhan; Nurul Yakin (Universitas Muhammadiyah Mataram, 2025)
Abstract: This study aims to analyze policy transformations and innovative programs in improving the quality of Islamic education through a Systematic Literature Review (SLR) approach. Literature sources were obtained from reputable databases, namely Scopus, DOAJ, and Google Scholar, with a limitation of publications from the last 10 years to ensure the relevance and actuality of the findings. The results of the analysis show that Islamic education has undergone significant development through the adoption of the Merdeka Curriculum, the digitization of learning, the strengthening of teachers' pedagogical competencies, and improvements in institutional governance. These transformations have contributed to improvements in learning quality and the effectiveness of education management. However, their implementation still faces obstacles, such as digital infrastructure inequality, suboptimal human resource readiness, cultural resistance, and a lack of conceptual models and long-term empirical evidence. The scientific contribution of this research lies in its latest mapping of the direction of transformation and gaps in Islamic education research. Its theoretical implications emphasize the need for a stronger conceptual framework to clarify the relationship between policy innovation, digitization, and improvements in the quality of Islamic education.Abstrak: Penelitian ini bertujuan menganalisis transformasi kebijakan dan program inovatif dalam meningkatkan mutu pendidikan Islam melalui pendekatan Systematic Literature Review (SLR). Sumber literatur diperoleh dari database bereputasi, yaitu Scopus, DOAJ, dan Google Scholar, dengan batasan publikasi 10 tahun terakhir guna memastikan relevansi dan aktualitas temuan. Hasil analisis menunjukkan bahwa pendidikan Islam telah mengalami perkembangan signifikan melalui adopsi Kurikulum Merdeka, digitalisasi pembelajaran, penguatan kompetensi pedagogis guru, serta perbaikan tata kelola lembaga. Transformasi tersebut berkontribusi pada peningkatan kualitas pembelajaran dan efektivitas pengelolaan pendidikan. Namun demikian, implementasinya masih menghadapi kendala, seperti ketimpangan infrastruktur digital, kesiapan SDM yang belum optimal, resistensi budaya, serta minimnya model konseptual dan bukti empiris jangka panjang. Kontribusi ilmiah penelitian ini terletak pada pemetaan terkini mengenai arah transformasi dan celah penelitian pendidikan Islam. Implikasi teoritisnya menegaskan perlunya kerangka konseptual yang lebih kuat untuk memperjelas hubungan antara inovasi kebijakan, digitalisasi, dan peningkatan mutu pendidikan Islam.